Analisis Strategi Pemasaran untuk Meningkatkan Tingkat Hunian Kamar di Brits Hotel Puri Indah dengan Menggunakan Analisis SWOT - Sri Ambar Wati; Henny Armaniah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
Brits Hotel Puri Indah faces challenges in increasing room occupancy amid fierce competition in the hospitality industry. This study aims to analyze effective marketing strategies for Brits Hotel Puri Indah using SWOT analysis. The methods employed include the IFE (Internal Factor Evaluation), EFE (External Factor Evaluation), IE (Internal-External), and SWOT matrices. The target market is focused on the corporate segment. The analysis results show that Brits Hotel Puri Indah has Strengths in the appropriate corporate market segment but faces Weaknesses in the suboptimal use of digital marketing technology. From the IFE analysis, the hotel obtained a score of 3.54, which is quite good, as it exceeds the threshold score of 2.5. Similarly, the EFE results are also satisfactory, with a score of 3.31, surpassing the 2.5 benchmark. In the IE matrix, the hotel is positioned in Cell I, which is categorized as